منهج القرآن والسنة في تعظيم الرسول صلى الله وسلم : دراسة تربوية تحليلية - Muhammad Jamil Sulaiman (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This research emphasizes the right approach of glorifying Prophet Muhammad PBUH, based on the methods in the Holy Qur'an and hadiths of the Prophet Muhammad PBUH, to achieve the components of the right methodology and to study them in a practical, and analytical way. The researcher adopted the inductive method, through past studies to collect Qur'anic verses that describe how to glorify Prophet Muhammad PBUH. Then, conducted an analytical study of the verses and hadiths related by studying the words of ancient and contemporary scholars. In this analytical method, after obtaining the glorifying verses regarding Prophet Muhammad PBUH in the Qur'an, the researcher explores the Qur'anic verses in order to attain formal semantics and practical aspects in educational dimensions. The definition of glorifying Prophet Muhammad PBUH is by protecting him from any humiliation in terms of deeds and words. Instead, he needs to be respected and glorified. This study revealed several features in the holy Qur'an about glorification of Prophet Muhammad PBUH, and several hadiths revealed these features through the life history of his companions. Moreover, the educational and applied dimensions of the glorification Prophet Muhammad PBUH might increase love and faith towards him by following his Sunnah. The first chapter discusses about the research plan. The second chapter discusses the meaning of glorifying Prophet Muhammad PBUH and explaining the views of scholars. The third chapter discusses the main purpose of this research by analysing the features of the Qur'anic education mentioned in the Qur'an. The fourth chapter discusses the educational and applied dimensions. The researcher have made a conclusion by presenting the results and recommendations